Study Implementation of Link and Match Teacher Expert from Dudika at Vocational Schools in Blitar Regency - Santoso, Heri Budi; Marsono, Marsono; Widiyanti, Widiyanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Vocational High School is an educational institution whose role is to prepare students to become middle-level workers to build the nation's economic sector. In the implementation of education, Vocational High Schools have the authority to determine their own curriculum to be used based on Dudika's needs. As an effort to fulfill these needs, SMK cooperates with Dudika through the implementation of expert teachers. This research is a multi-case study that describes and compares the implementation of Link and Match Guru Expert from PT Medion Ardhika Bhakti at SMK Negeri I Kademangan and SMK Negeri | Udanawu. This study aims to describe the process of planning, implementation, preparation, form of MoU, evaluation and impact of the implementation of expert teachers. Data collection techniques were carried out through interviews, observations and field notes on the activities of expert teachers.